Flexible Control Architecture For Mobile Robot Navigation As Campus Guide - Loh, Kwang Hooi (2008)
The goal of this research is to transform a generic mobile-robot platform into a campus service robot. The commercial P2AT robot from ActivMedia Robotic Inc (www.activemedia.com) is used as the experimental platform.